Optimal fertilization in rainfed corn regarding nutrient removal and soil diagnosis in small plots - García-Martínez, René; González-Félix, Eduar Antonio; Ayllón-Benítez, Julio César; García-Urbina, Jesús; Sánchez-Aguilar, Hotón (Revista Mexicana de Ciencias Agrícolas, 2026)
In the south of the State of Mexico, Mexico, small corn producers obtain low yields (<5 Mg ha-1) due to deficiencies in nutrition management. The research aimed to determine the fertilization dose for small rainfed corn plots, considering the condition of soil fertility and nutrient extraction by grain and stover. The research was conducted in Villa de Allende, State of Mexico, in two plots with different fertilization management. Plot A received 1 t of bovine manure compost and plot B received 30 kg of a urea + triple 17 (N-P-K) mixture. Based on soil fertility diagnosis and nutrient removal by grain and stover, fertilization doses were defined. In both plots, OM and N contents were low and Fe levels were adequate. In plot A, the soil presented high levels of P, K, Ca and Mg. The grain and stover extracted high amounts of N and K. In plot A, the need for fertilizers was concentrated on N, Fe and Zn, whereas in plot B, it was N, P, K, Ca, Mg, Fe and Zn. This generated a reduction in the need for fertilizers; in the first case, it represented a 48% saving in costs. This approach contributes to improving productivity, reducing costs and reducing environmental impact in small-scale agriculture.